Thermal Stress Coupling Analysis of Ventilated Disc Brake Based on Moving Heat Source - Gongyu Pan; Rongyu Cai (Advances in Materials Science and Engineering)
There is a thermomechanical coupling phenomenon in the braking process of vehicle disc brakes. Since the solution time of the direct coupling method is long and it is hard to converge, it is not suitable for analyzing heavy-load braking conditions with long braking time. Meanwhile, the sequential coupling method based on fixed heat source cannot achieve the rotation of friction heat source of the brake disc or accurately simulate the change of temperature. Therefore, Abaqus user subroutine is invoked to achieve the heat source rotation. The results of the simulated temperature field are compared with the results of the complete thermodynamic coupling method, the sequential coupling method based on fixed heat source and dyno test. The comparison shows that the new method combines the advantages of the first two methods and has a better engineering value.